1990
DOI: 10.1007/bf00189729
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of visual inter and intrahemispheric cortico-cortical connections in five native Chilean rodents

Abstract: Previous studies of the visual cortical organization in the rat and other rodent species have raised the possibility that the visual cortical plan in the rat is common to a large number of species within the order. We have tested this idea by comparing the visual plan in the rat to cortical subdivision schemes obtained from five native Chilean rodent species, including members of the Cricetidae family within the Miomorph group, as well as from the Octodontidae family within the Caviomorph group. Cortical subdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Similar issues arise for the infragranular distribution of callosal neurons that has been described in medial portions of striate cortex in the rat (Olavarria and Van Sluyters, 1983), as well as other rodent species (mouse: Olavarria and Van Sluyters, 1984;hamster: Dursteler et al, 1979;Rhoades et al, 1987; Octodon degus: Bravo et al, 1990). At present it is not known whether callosal linkages in medial striate cortex are organized in a mirror-symmetric fashion with respect to the midline, or in some other way.…”
mentioning
confidence: 77%
“…Similar issues arise for the infragranular distribution of callosal neurons that has been described in medial portions of striate cortex in the rat (Olavarria and Van Sluyters, 1983), as well as other rodent species (mouse: Olavarria and Van Sluyters, 1984;hamster: Dursteler et al, 1979;Rhoades et al, 1987; Octodon degus: Bravo et al, 1990). At present it is not known whether callosal linkages in medial striate cortex are organized in a mirror-symmetric fashion with respect to the midline, or in some other way.…”
mentioning
confidence: 77%
“…Mouse extrastriate cortex also differs from that in many nonprimate species (i.e., quoll, hedgehog, guinea pig, rabbit, flying fox, opossum, squirrel, tree shrew, cat) in which V1 is adjoined on the lateral side by a single area, V2 (Kaas et al, 1970(Kaas et al, , 1989Hall et al, 1971;Towns et al, 1977;Payne, 1993;Rosa, 1999;Kahn et al, 2000), and therefore has a "simple" organization . However, mouse extrastriate cortex is similar to that in species with a "simple" organization, in that V1 is adjoined on the medial side by parastriate or splenial visual areas, which in hedgehog, rat, hamster, degu, guinea pig, and cat receive direct V1 input and contain visually responsive neurons (Kalia and Whitteridge, 1973;Choudhury, 1978;Gould and Ebner, 1978;Olavarria and Mendez, 1979;Bravo et al, 1990;Olavarria and Montero, 1990;Spatz et al, 1991;Montero, 1993). Thus, mouse extrastriate cortex is "simple" in the sense that it has a single V2-like area, LM, on the lateral side of V1, but is "complex" in that lateral V1 is adjoined by multiple visual areas.…”
Section: Vertical Meridian Representation In V1 Is Confined To V1/lm mentioning
confidence: 92%
“…Previous single and multitracer experiments in mouse, rat, hamster, degu, guinea pig, and squirrel have labeled similar targets, which were considered either distinct areas Montero, 1989, 1990;Bravo et al, 1990;Spatz et al, 1991;Montero, 1993) or repeating modules within a single area, V2 (Kaas et al, 1989;Malach, 1989;Rumberger et al, 2001). By mapping the connections from a wide range of topographic locations, we found that, unlike stripes in monkey V2, which create map discontinuities within a single global map (Roe and Ts'o, 1995), each of the labeled targets contains a complete map of the entire visual field, and together the maps form a seamless mosaic of extrastriate areas (Fig.…”
Section: Extrastriate Cortex Contains Multiple Visuotopic Areasmentioning
confidence: 99%
“…In fact, uneven distribution of callosal and striate-peristriate connections are common features of cortical organization among placental mammals (see, e.g., Olavarria and Montero 1984;Sesma et al 1984;Cusick et al 1985;Bravo et al 1990). The radial organization of commissural connections in M.…”
Section: Comparison With Callosal Mammalsmentioning
confidence: 99%